2019
DOI: 10.1016/j.bonr.2019.100207
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic proteins: Their role in regulating osteoclast differentiation

Abstract: The ability to create recombinant bone morphogenetic proteins (BMPs) in recent years has led to their rise as a common clinical adjuvant. Their application varies, from spinal fixation to repairing palatal clefts, to coating implants for osseointegration. In recent years questions have been raised as to the efficacy of BMPs in several of these procedures. These questions are due to the unwanted side effect of BMPs on other cell types, such as osteoclasts which can resorb bone at the graft/implant site. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 101 publications
(161 reference statements)
0
34
0
Order By: Relevance
“…It has been reported that in BMP signaling transduction, the choice of whether the SMAD or non-SMAD signaling pathway should be activated depends on the way in which BMP binds to the receptor complex. If BMP binds to a preformed BMP receptor type I/BMP receptor type II complex, the SMAD signaling pathway is expressed [ 88 ]. On the other hand, if BMP binds to BMP receptor type 1 or BMP receptor type II to recruit the other, the non-SMAD signaling pathway is expressed [ 71 , 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that in BMP signaling transduction, the choice of whether the SMAD or non-SMAD signaling pathway should be activated depends on the way in which BMP binds to the receptor complex. If BMP binds to a preformed BMP receptor type I/BMP receptor type II complex, the SMAD signaling pathway is expressed [ 88 ]. On the other hand, if BMP binds to BMP receptor type 1 or BMP receptor type II to recruit the other, the non-SMAD signaling pathway is expressed [ 71 , 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…BMP has been reported to affect osteoclastogenesis indirectly and directly as well as exert osteoinductive effects on bone formation. 20,21 In this study, rhBMP2-induced ectopic bone in Smurf2 −/− mice exhibited increases in the TRAP-positive area and number of osteoclasts. In vitro, Smurf2 −/− BMSCs showed enhanced Rankl expression when cultured in rhBMP2-supplemented medium.…”
Section: Smurf2mentioning
confidence: 51%
“…Osteoblastic lesions arise from cancer-induced signalling via bone morphogenetic proteins (BMPs), fibroblast growth factor and TGFβ resulting in osteoblast activation [ 24 ]. Expression of BMP-2, -4, -6 and -7 is elevated within bone metastases [ 33 ] within which BMPs can induce the osteogenic differentiation of osteoblasts [ 34 ].…”
Section: Bone Homeostasis and The Vicious Cyclementioning
confidence: 99%